Comparative evaluation of accuracy of three different electronic apex locators in the presence of various endodonticirrigants: An in vitro study - A. Nagrani; A. B. Tandale; S. Mulay; Sh. Khade; D. Shah (Эндодонтия Today, 2024)
AIM AND OBJECTIVES. To evaluate and compare the accuracy of Root ZX, Raypex6, and I Root and electronic apex locators in the presence of NaOCl (3%), Citric acid (10%), MTAD and Green tea extract as endodontic irrigants.MATERIAL AND METHOD. Sixty single rooted human permanent teeth were used for the study. Access cavities were prepared and the teeth were decoronated. Teeth were divided as follows: Group I-Root ZX apex locator (n=20), IA – NaOCl 3% endodontic irrigant (n=5), IB – Citric Acid 10% endodontic irrigant (n=5), IC – MTAD endodontic irrigant (n=5), ID- Green Tea extract endodontic irrigant (n=5). Group II: Raypex 6 apex locator (n=20). IIA – NaOCl 3% endodontic irrigant (n=5), IIB – Citric acid 10% endodontic irrigant (n=5). IIC – MTAD endodontic irrigant (n = 5), IID – Green tea extract endodontic irrigant (n=5). Group III-i-ROOT apex locator (n=20). IIIA – NaOCl 3% endodontic irrigant (n=5), IIIB – Citric Acid 10% endodontic irrigant (n=5), IIIC – MTAD endodonticirrigant (n=5), IIID – Green tea extract endodontic irrigant (n=5). The actual working length was determined using a 15 K file and the working model was prepared using Alginate in a rectangular box. The teeth were embedded into the working model and the electronic measurements were made with each electronic apex locator. The data was collected, analyzed and subjected to statistical analysis.RESULTS. No significant difference was found when Raypex 6 apex locator was used along with all the endodontic irrigants except green tea extract. Root ZXshowed statistically significant difference with green tea extract and MTAD. I-root showed statistically significant difference with all the irrigants except green tea extract.CONCLUSION. Citric acid 10% was consistently accurate when assessed with all the three apex locators, whereas Green tea extract demonstrated the least accurate readings with all apex locators.